Opportunities for early intervention: bringing perpetrators of family violence into view
This report calls for earlier and more proactive intervention in family violence, arguing that while family violence has finally come to attention as a systemic wrong in need of a National Plan, a significant gap exists in our collective response. Executive summary This report turns the spotlight on perpetrators of family violence. In doing so, it calls for earlier and more proactive intervention - explaining that, while family violence has finally come to attention as a systemic wrong in need of a National Plan, a significant gap exists in our collective response. Equally, while victims of family violence must remain our priority, these victims will also remain at risk unless we step back and widen our gaze. In other words, until we adjust the lens and bring those who use violence and coercion more clearly into view - until we intervene at the source of the problem - the cycle of this violence will simply roll on. This may manifest in assaults against the same or subsequent partners, in the damaging effects we know are experienced by children, in the behaviour of  adolescents, or in the tragic escalation that can devastate an entire community. Either way, it will manifest as core business in our courts and as an ongoing drain on our economic and social wellbeing